Importância da leitura prazerosa na Educação Infantil: o encantamento do Era Uma Vez... - Sabino Neta, Francisca Valdira (2016)
This study mainly presents an analysis of reading experiences in nursery school as a learning instrument that besides causing the incantation and pleasure, leading raising awareness to the student affording him to feel producer inserted into the told story. The article seeks the reflection about the importance of reading practice in in early childhood, as supportive learning in nursery education. It shows that the experience of the pleasure of reading should start at home and improving at the school with diverse instruments, motivators of the sensitivity that stimulate and provide the taste and reading desire. The article offers an analysis about the importance of reading exerts in the development of skills and competencies to children aged zero to six years old. Presents the reading as a pedagogical practice that develops the form of the child to see herself, others and the world. The work presents suggestions of methods and strategies that may be used by the teacher in the process of encouraging the formation of future readers. In this article was used the bibliographic research in which weaves a dialogue between authors who study about the subject in question as well as field research, which was conducted with teachers who work in nursery school. Through the research, it was concluded that reading is fundamental tool and necessary in the nursery school classroom. Moreover, it was observed that the teachers use in their readers times routine, however, although they know the importance that it has, use a few methods and strategies in story telling which could make this repetitive time, and consequently will not be developed in the child the fascination for reading.